A two-storey structured photoanode of a 3D Cu2ZnSnS4/CdS/ZnO@steel composite nanostructure for efficient photoelectrochemical hydrogen generation. Issue 37 (1st September 2015) - Choi, Youngwoo; Baek, Minki; Zhang, Zhuo; Dao, Van-Duong; Choi, Ho-Suk; Yong, Kijung
Abstract : A two-storey structured photoanode of a 3D Cu2 ZnSnS4 (CZTS)/CdS/ZnO@steel composite nanostructure has demonstrated highly efficient photoelectrochemical hydrogen generation. Abstract : A two-storey structured photoanode of a 3D Cu2 ZnSnS4 (CZTS)/CdS/ZnO@steel composite nanostructure has been fabricated by using the solution method and demonstrated highly efficient photoelectrochemical hydrogen generation due to its contraption in the structure for sufficient light absorption as well as the three step-down band alignments for efficient charge separation and transport. This composite structure is composed of two storeys: the upper storey is the CZTS/CdS/ZnO hetero-nanorods (NRs) covered on the stainless steel mesh; the bottom storey is the CZTS/CdS/ZnO hetero-NRs grown on the FTO glass. The CZTS/CdS/ZnO hetero-NRs have cascade band gaps decreasing from 3.15 to 1.82 eV, which gives them efficient charge transfer and broad photoresponse in the UV to near-IR region, resulting in 47% IPCE in a wide light region from 400 to 500 nm; and the stainless steel mesh serves not only as a conductor for charge transport, but also as a skeleton of the grid structure for absorbing more light. The related mechanism has been investigated, which demonstrates that the two-storey CZTS/CdS/ZnO@steel composite nanostructure would have great potential as a promising photoelectrode with high efficiency and low cost for PEC hydrogen generation.